A selective review of foreign direct investment theories - Dinkar Nayak; Rahul N. Choudhury (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2014)
Several theories have been put forward by the researchers to explain foreign direct investment. However, no single theory fits the different types of direct investment or the investment made by a particular multinational corporation or country in any region. This paper traces the evolution of the theories of foreign direct investment (FDI) during the past few decades. An attempt is also made to ex plain the growth phenomenon of Third World multinational companies. The applicability of the theory differs with the type and origin of investment. Nevertheless, all these theories are unanimous in their view that a firm moves abroad to reap the benefits of the advantages in the form of location, firm-specific or internationalization of markets.
Keywords: F21; F23; F36; 330; Foreign direct investment; internalization; MNCs; motivation; trade